New Perspectives in the Exploration of Korsakoff’s Syndrome: The Usefulness of Neurophysiological Markers - Brion, Mélanie; Pitel, Anne-Lise; D’Hondt, Fabien (Frontiers in Psychology, 2016)
This perspective aims at underlining the usefulness of event-related potentials (ERP) to better understand the brain correlates of Korsakoff’s syndrome (KS), a neuropsychiatric disease characterized by severe memory impairment and most frequently resulting as a neurological complication of alcohol-dependence (AD). While ERP have been broadly used in AD, it has up to now been very little applied in KS or in the comparison of KS and AD. Within the framework of dual-process models, an influential theory postulating that addictive states result from an imbalance between under-activated reflective system and over-activated automatic-affective one, this paper proposes: (1) a brief synthesis of the main results of ERP studies in AD and KS, and (2) new research avenues using ERP to identify the electrophysiological correlates of cognitive and emotional dysfunction in KS. These experimental perspectives aim at exploring the continuity hypothesis, which postulates a gradient of impairments from AD to KS. We conclude on the possibility of developing neuropsychological strategies with electrophysiological follow-up to ensure KS diagnosis and test the efficacy of patient’s neurocognitive rehabilitation.